(untitled) (Applied Biological Research, 2020)
The study was conducted to assess the effect of animal-fat supplementation on energy utilization in Large White Yorkshire (LWY) pigs fed with corn soya-based ration as per the requirements of NRC (2012). Twenty weaned piglets were randomly divided into two groups and allotted to one of the wo dietary treatments i.e. control ration (as per NRC, 1998) and ration supplemented with animal fat @ 5%. A digestibility trial was conducted following total collection method and gross energy was estimated using bomb calorimeter. The results revealed that gross energy of feed and faeces were 4144, 4410 and 4102, 4090 kcal kg-1, respectively, for control and animal feed supplemented treatments. The gross energy converted as digestible energy was 85.8 and 87.3% and the calculated digestible energy of feed was 3558.1 and 3848.8 kcal kg-1for the respective groups. The result showed that the animal-fat supplementation (5%) increased the efficiency of energy utilization in growing LWY pigs.